Do Equity Investors Care about Environment, Social and Governance (ESG) Disclosure Performance? Evidence from India. Issue 6 (December 2022) - Mulchandani, Ketan; Mulchandani, Kalyani; Iyer, Geetha; Lonare, Alaknanda
Sustainability reporting is an essential feature for firms looking for business opportunities. We investigated whether and how environmental, social and governance performance disclosures impact the cost of equity capital, individually and in aggregate. Data for 89 Indian firms listed on exchange during 2017–2020 is considered for the study. Fixed-effect panel regression is applied to data for examining the relationship between ESG and the cost of equity capital. Results of the study show that ESG performance disclosure negatively impacts cost of equity capital, providing the firm with capital at a lower cost. ESG disclosures create long-term value for investors and reduce information asymmetry, thereby building investors' confidence.